Bletilla striata polysaccharide composite hydrogel capable of slowly releasing salvianic acid A sodium as well as preparation method and application of bletilla striata polysaccharide composite hydrogel

By combining Bletilla polysaccharide with chitosan and β-glycerol sodium phosphate to form a sustained-release hydrogel and incorporating Salvia sodium sodium, the problem that existing wound dressings cannot provide a humid environment and low absorption rate of Bletilla polysaccharide is solved, and the effects of wound healing and sustained-release of small molecule drugs are achieved.

CN119746142APending Publication Date: 2025-04-04ZHEJIANG QINGRONG BIOTECHNOLOGY DEV CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411912747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing wound dressings cannot effectively provide a humid environment, resulting in secondary wound damage, and the absorption rate of Bletilla polysaccharide is low, making it difficult to exert its efficacy.

Method used

A Bletilla polysaccharide composite hydrogel was developed to form a hydrogel preparation with sustained release effect by combining with chitosan and sodium β-glycerol phosphate, and incorporated into it to achieve sustained release of small molecule drugs and wound healing.

Benefits of technology

The hydrogel has good biocompatibility and low cytotoxicity and no immunogenicity. It can absorb wound effusion, promote wound healing, and achieve long-term sustained release of sodium danshin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746142A_ABST
    Figure CN119746142A_ABST
Patent Text Reader

Abstract

The invention discloses bletilla striata polysaccharide composite hydrogel capable of slowly releasing salvianic acid A sodium, a preparation method and application, and belongs to the technical field of hydrogel. A salvianic acid A sodium solution is directly added into a chitosan solution to be fully stirred, then chitosan loaded with salvianic acid A sodium is cross-linked with beta-sodium glycerophosphate, bletilla striata polysaccharide is cross-linked with chitosan, and BSP / CS / beta-GP (at) SDSS composite hydrogel doped with salvianic acid A sodium micromolecule medicine is formed. The composite hydrogel has the pore diameter of 20-30 [mu] m, so that the composite hydrogel is endowed with relatively strong crosslinking density, and the slow release of micromolecular salvianic acid A sodium for 53h can be carried out. The hydrogel has low adhesion, is not easy to cause secondary injury to a wound, can absorb wound exudate and keep the wound moist, has excellent antibacterial performance and no cytotoxicity, and is beneficial to proliferation and migration of epidermal cells. The medicine can be used as a treatment medicine for diseases such as acute wound surfaces and chronic wound surfaces and can promote wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of hydrogel preparation technology and biomedical polymer materials, and in particular to a bletilla striata polysaccharide composite hydrogel capable of sustained-release sodium danshensu, a preparation method and application thereof. Background Art

[0002] As the first line of immune defense and the largest organ of the human body, the skin is vulnerable to external damage. Appropriate wound management tools and effective wound care materials may accelerate the healing of skin wounds. At present, traditional wound dressings, such as bandages, gauze, cotton flannel, etc., have occupied the main market of wound dressings. Although traditional wound dressings can effectively absorb exudates secreted by wounds, the fiber structure of these dressings is loose, and frequent dressing changes are required to prevent infection. In addition, traditional wound dressings cannot provide a proper moist environment for wounds, resulting in secondary wound damage. Therefore, an ideal wound care material must be flexible, stable, biodegradable and widely used, with the potential to stop bleeding, keep wounds moist and absorb exudates.

[0003] According to the book "Compendium of Materia Medica·Cao 1·Bletilla striata" written by Li Shizhen in the Ming Dynasty, "its root is white and grows together, so it is named Bletilla striata." According to traditional Chinese medicine, Bletilla striata is bitter, astringent, cold, sticky and astringent, enters the lung, stomach and liver meridians, astringent and hemostatic, and has the effects of reducing swelling and promoting tissue regeneration. Modern scientific research has shown that the fresh tuber of Bletilla striata contains 14.6% water, 30.48% starch and 1.5% glucose. It also contains volatile oil and mucus. Bletilla striata polysaccharide (BSP) is a polysaccharide rich in aqueous solution in the bulb of Bletilla striata. Its chemical composition is glucomannan, which is composed of mannose and glucose connected by 1,2- or 1,4-glycosidic bonds. Bletilla striata polysaccharide has biological activities such as anti-inflammatory, procoagulant, antiviral, anti-tumor and antioxidant, and has the characteristics of functional sustained release, local retention, self-degradability, non-irritation, non-toxic side effects, abundant resources, and cheap and easy to obtain. Bletilla striata polysaccharide is an excellent natural thickener, a relatively safe pharmaceutical raw material, a pharmaceutical excipient with excellent performance, and a biomedical material with considerable development prospects.

[0004] However, there are currently two main methods for using Bletilla striata polysaccharide: taking it orally or applying it externally with water or other Chinese herbal ingredients. Due to the low absorption rate of Bletilla striata polysaccharide, it is difficult for it to exert its due therapeutic effect. Therefore, it is worth exploring the development of Bletilla striata polysaccharide preparations for specific diseases to achieve effective utilization of Bletilla striata polysaccharide.

[0005] Hydrogel is a type of hydrophilic polymer material with a three-dimensional network structure. It has a unique 3D structure, high permeability, and tissue-like mechanical properties. It has received extensive attention in recent years. The hydrogel system composed of biomacromolecules has better tissue compatibility and occupies an important position in biomedical materials. In recent decades, research on wound dressings has shown that hydrogels can provide a moist microenvironment, stimulate endogenous cell proliferation, maintain gas exchange required for tissue respiration, and repair epidermal or dermal damage.

[0006] Chitosan (CS) is the only positively charged linear natural polymer in nature. Its basic unit is acetylglucosamine. The amino and hydroxyl groups on the deacetylated chitosan have high reactivity and are easily protonated to adsorb anions. Studies have shown that chitosan has physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, and anti-inflammatory. It is widely used in the food industry, daily chemicals, and pharmaceutical industries. It has been reported that chitosan can form a thermosensitive hydrogel material with β-sodium glycerophosphate (β-GP), which can achieve the transition from sol to gel at 37°C. However, the hydrogel composed of only these two substances has poor mechanical properties and degrades too quickly in the body, which is not conducive to the sustained release of drugs.

[0007] Danshensu sodium (SDSS) is a small molecule drug with a molecular weight of 222.17, which has stable performance and high absorption and utilization. It has anti-inflammatory, antioxidant, anti-apoptotic and free radical scavenging effects. At present, the in vitro application of danshensu sodium is limited to creams and lotions. This method is simple and convenient, but it is not conducive to the stability of drug concentration in the affected area and the effective utilization of ingredients.

[0008] The purpose of the present invention is to provide a better sodium danshensu sustained-release carrier. The hydrogel has better physical and chemical properties such as structure and tissue adhesion, and also has a better sustained-release effect of the small molecule drug sodium danshensu. Moreover, the hydrogel has good biocompatibility, low cytotoxicity, and no immunogenicity. It can absorb a large amount of wound exudate and effectively promote wound healing. Summary of the invention

[0009] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a composite hydrogel of bletilla striata polysaccharide that can sustain the release of sodium danshensu and its application, to construct a hydrogel preparation doped with bletilla striata polysaccharide to solve the problem of efficient utilization of bletilla striata polysaccharide, to effectively develop the external value of bletilla striata polysaccharide, and to incorporate sodium danshensu to form a small molecule drug sustained-release system. The composite hydrogel can be applied externally for skin repair treatment and has broad application prospects in the treatment of in vitro wound healing.

[0010] The technical solution adopted by the present invention is specifically as follows:

[0011] A method for preparing a bletilla striata polysaccharide composite hydrogel capable of sustained-release sodium danshensu comprises: preparing a chitosan solution, adding a sodium danshensu solution to the chitosan solution, and mixing a β-sodium glycerophosphate solution with the chitosan solution under ice bath conditions to obtain a mixed solution. A bletilla striata polysaccharide solution is prepared, and under normal temperature conditions, the mixed solution is added to the bletilla striata polysaccharide solution, mixed evenly, and the mixed solution and the bletilla striata polysaccharide solution are cross-linked in a molecular entanglement manner to obtain a bletilla striata polysaccharide composite hydrogel. Preferably, the mass ratio of chitosan: sodium glycerophosphate: bletilla striata polysaccharide in the composite hydrogel is 3: (7-15): (6-12), and the mass ratio of chitosan: sodium danshensu is (18-22): 1; the cross-linking temperature is 20-37°C, and the cross-linking time is 1-5 min. The bletilla striata polysaccharide composite hydrogel of the present invention achieves gelation within 2 min at 37°C.

[0012] The bletilla striata polysaccharide hydrogel of the present invention has a pore size of 10-50 μm, preferably 20-30 μm, which gives the bletilla striata polysaccharide composite hydrogel a stronger cross-linking density.

[0013] The Bletilla striata polysaccharide composite hydrogel of the present invention can be used as a drug sustained-release stent or used to prepare a medicament for promoting wound healing in vitro. In vitro wounds include acute wounds (burns, abrasions, surgical trauma, lacerations, battlefield penetrating wounds) and chronic wounds.

[0014] The skin wound healing effect of the bletilla striata polysaccharide hydrogel involved in the present invention is achieved by establishing a mouse skin wound model to study the effect of the bletilla striata polysaccharide hydrogel on accelerating wound healing in the wound healing process.

[0015] The beneficial effects of the present invention are:

[0016] (1) The polymer raw materials used in the present invention are all of natural origin and are commonly used biomedical materials with good biocompatibility and are biodegradable in vitro.

[0017] (2) The raw materials involved in the present invention are low in cost, the material preparation steps are simple, cross-linking is achieved by molecular entanglement, no cross-linking agent is added, and the material is easy to synthesize and produce industrially, thus having commercial application value.

[0018] (3) The hydrogel material of the present invention has the property of rapid gelation at room temperature. Compared with the chitosan-β-sodium glycerophosphate thermosensitive hydrogel, the hydrogel composite material obtained by the present invention can achieve gelation at 37°C in 2 minutes, and can achieve excellent in situ gelation effect.

[0019] (4) The hydrogel composite material of the present invention can be used as a drug sustained-release stent, which is beneficial to achieve the long-term sustained-release of the small molecule drug sodium danshensu, and can be used in the fields of tissue damage repair, etc., and has broad application prospects.

[0020] (5) The Bletilla striata polysaccharide hydrogel of the present invention has a significant effect on promoting wound healing, meets the requirements of an ideal skin healing hydrogel dressing, has certain biological activity, is highly safe, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1 The Bletilla striata polysaccharide composite hydrogel capable of sustained-release of sodium danshensu obtained in Example 1 of the present invention (A) is placed conventionally, and (B) is inverted;

[0023] Figure 2 This is a scanning electron microscope image of the Bletilla striata polysaccharide composite hydrogel BSP / CS / β-GP@SDSS loaded with sodium danshensu obtained in Example 1 of the present invention, wherein (A) and (B) correspond to different magnifications respectively;

[0024] Figure 3 This is a rheological property test diagram of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel BSP / CS / β-GP@SDSS obtained in Example 1 of the present invention;

[0025] Figure 4 This is a test diagram of the water absorption performance of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel BSP / CS / β-GP@SDSS obtained in Example 1 of the present invention;

[0026] Figure 5 This is a diagram of drug sustained release efficiency of the Bletilla striata polysaccharide composite hydrogel BSP / CS / β-GP@SDSS loaded with sodium danshensu obtained in Example 1 of the present invention;

[0027] Figure 6 This is a graph showing the antibacterial test results of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel BSP / CS / β-GP@SDSS obtained in Example 1 of the present invention. In this experiment, Staphylococcus aureus was used as the research object. In the annotations, BSP / CS / β-GP represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel, and BSP / CS / β-GP@SDSS represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel. The numbers represent the dilution multiples of the hydrogel extract during the experiment, 1 for dilution by one time, 2 for dilution by two times, and so on.

[0028] Figure 7This is a diagram showing the cytotoxicity test results of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel obtained in Example 1 of the present invention, with a human immortalized epidermal cell line as the research object. In the annotations, BSP / CS / β-GP represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel, and BSP / CS / β-GP@SDSS represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel. The numbers represent the dilution multiples of the hydrogel extract during the experiment, 1 for dilution by one time, 2 for dilution by two times, and so on.

[0029] Figure 8 This is a cell proliferation experiment result diagram of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel obtained in Example 1 of the present invention, with the human immortalized epidermal cell line as the research object. In the annotation, BSP / CS / β-GP represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel, and BSP / CS / β-GP@SDSS represents the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel. The numbers represent the dilution multiples of the hydrogel extract during the experiment, 1 for dilution by one time, 2 for dilution by two times, and so on.

[0030] Fig. 9 This is a diagram showing the results of a cell migration experiment of a sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel obtained in Example 1 of the present invention, with a human immortalized epidermal cell line as the research object, BSP / CS / β-GP representing the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel, and BSP / CS / β-GP@SDSS representing the extract of the sodium danshensu-loaded Bletilla striata polysaccharide composite hydrogel;

[0031] Fig.10 This is a rat wound healing experiment result diagram of the Bletilla striata polysaccharide composite hydrogel loaded with sodium danshensu obtained in Example 1 of the present invention, where BSP / CS / β-GP@SDSS represents the Bletilla striata polysaccharide composite hydrogel loaded with sodium danshensu;

[0032] Fig.11 It is a graph showing the results of HE staining and Masson staining of a rat wound healing experiment of the Bletilla striata polysaccharide composite hydrogel loaded with sodium danshensu obtained in Example 1 of the present invention. BSP / CS / β-GP@SDSS represents the Bletilla striata polysaccharide composite hydrogel loaded with sodium danshensu. DETAILED DESCRIPTION

[0033] (1) Preparation of hydrogel

[0034] Comparative Example 1, preparation of Bletilla striata polysaccharide / chitosan / β-sodium glycerophosphate hydrogel (BSP / CS / β-GP):

[0035] A mixed solution of sodium β-glycerophosphate and chitosan was prepared, wherein the concentration of sodium β-glycerophosphate before mixing was 0.6 g / mL (w / v), the solvent was pure water, the concentration of chitosan before mixing was 0.02 g / mL (w / v), the solvent was 0.1 M acetic acid, and the pH value of the solution after mixing was 7.2±0.2, wherein the unit of w / v was g / mL. The method for preparing a mixed solution of sodium β-glycerophosphate and chitosan is as follows: under ice bath stirring conditions, the sodium β-glycerophosphate solution is added dropwise to the chitosan solution, the volume ratio of the sodium β-glycerophosphate solution to the chitosan solution is 1:10, and a mixed solution of sodium β-glycerophosphate and chitosan is obtained; a bletilla striata polysaccharide solution is prepared, the concentration of bletilla striata polysaccharide in the solution is 0.01 g / mL (w / v), and the solvent is pure water; under room temperature conditions, the mixed solution of sodium β-glycerophosphate and chitosan is added to the bletilla striata polysaccharide solution, the mixture is evenly mixed, the volume ratio is , and the mixture is placed in a 37°C water bath to obtain a bletilla striata polysaccharide composite hydrogel.

[0036] Example 1, preparation of Bletilla striata polysaccharide / chitosan / β-sodium glycerophosphate hydrogel loaded with danshensu sodium (BSP / CS / β-GP@SDSS):

[0037] A sodium danshensu solution was prepared with a concentration of 0.01 g / mL (w / v) and pure water as the solvent. The sodium danshensu solution was added into the chitosan solution with a mass ratio of chitosan: sodium danshensu of 20:1. Then, sodium β-glycerophosphate and chitosan were mixed. The remaining steps were the same as those in Comparative Example 1.

[0038] Example 2 is different from Example 1 in that the concentration of β-sodium glycerophosphate before mixing is 0.8 g / mL (w / v), the concentration of chitosan before mixing is 0.04 g / mL (w / v), and the concentration of Bletilla striata polysaccharide in the Bletilla striata polysaccharide solution is 0.015 g / mL (w / v).

[0039] Example 3 is different from Example 1 in that the concentration of the sodium danshensu solution is 0.02 g / mL (w / v).

[0040] (2) Hydrogel micromorphology analysis

[0041] The microstructure of the hydrogel sample prepared in Example 1 was observed using a scanning electron microscope (SEM, ZEISS GeminiSEM 300, Germany). The SEM image shows ( Figure 2 ), the hydrogel samples all showed a uniform three-dimensional skeleton structure and a large number of micropores after freeze-drying. This special structure can maintain physiological wound moisture and allow gas exchange, which can promote the transfer of nutrients and cell waste in wound defects and promote cell proliferation. The network distribution of the hydrogel is uniform, and the pore size is also relatively uniform, with a pore size of about 20-30μm. The extremely small pore size is conducive to the loading of small molecule drugs and realizes the long-term sustained release of drug molecules.

[0042] (3) Analysis of viscoelastic properties of hydrogels

[0043] The viscoelastic properties of the hydrogel sample prepared in Example 1 were characterized using a rheometer (TA DHR-2, USA). Rheological measurements were used to characterize the adhesion of the hydrogel. The rheological results showed that ( Figure 3 ), the hydrogel viscosity is 10 -2 Pa·s, which is a low-adhesion hydrogel. Hydrogels used as wound dressings do not need high adhesion to ensure that no secondary damage to the skin occurs when the wound dressing is removed. The results of rheological tests show that the viscosity of the BSP / CS / β-GP@SDSS hydrogel decreases with increasing BSP concentration, achieving the requirement of low adhesion properties for wound dressing hydrogels.

[0044] (4) Analysis of water absorption properties of hydrogel

[0045] Definition: Water absorption rate = mass difference before and after water absorption / mass before water absorption * 100%;

[0046] The results show that Figure 4 ), BSP / CS / β-GP@SDSS hydrogel reaches the maximum water absorption in about 4-6 hours, and the maximum water absorption is 170%. The hydrogel stops losing water in about 12 hours and reaches equilibrium swelling. The water absorption property of the hydrogel enables it to absorb exudate in the early stage of wound healing. The hydrogel's ability to not absorb water excessively ensures that the hydrogel will not dissolve due to excessive water absorption. In addition, this swelling property allows the hydrogel to be used as a carrier for drug release on the one hand, and on the other hand, the low water absorption ensures that the loaded drug will not be released quickly.

[0047] (5) Analysis of release of sodium danshensu

[0048] The in vitro drug release kinetics of the SDSS-loaded hydrogel prepared in Example 1 was studied by dialysis, using a 37°C water bath to simulate the temperature of the human body surface. Figure 5 ), BSP / CS / β-GP@SDSS released SDSS rapidly within the first 10 hours during sustained release. The rapid release behavior in the initial stage is a common phenomenon of hydrophilic hydrogel carriers. Because the drug easily falls off the surface of the material, the release rate of sodium danshensu is also faster in the early stage, and then the release rate slows down. The total release time of SDSS is 53 hours. The long-term sustained release of small molecule drugs is achieved, proving that the hydrogel can be used as a potential small molecule drug release carrier.

[0049] (6) Analysis of antibacterial properties of hydrogel

[0050] The 96-well plate method was used to verify the antibacterial properties of the BSP / CS / β-GP and BSP / CS / β-GP@SDSS hydrogel samples prepared in Comparative Example 1 and Example 1 against Staphylococcus aureus. In this experiment, the PBS extract of the hydrogel was used instead of the hydrogel to complete the experiment. As shown in the figure ( Figure 6 ), within 72 hours, the viability of Staphylococcus aureus in experimental groups one and two was lower than that in the control group, and the bacterial activity gradually weakened with the extension of time. This shows that the antibacterial performance of BSP / CS / β-GP@SDSS hydrogel is further enhanced compared with BSP / CS / β-GP, and BSP / CS / β-GP@SDSS can provide long-term antibacterial effect.

[0051] (7) Hydrogel cytotoxicity analysis

[0052] The CCK-8 in vitro method was used to detect the toxic effects of the BSP / CS / β-GP and BSP / CS / β-GP@SDSS hydrogel samples prepared in Comparative Example 1 and Example 1 on human immortalized keratinocytes (HaCat). In this experiment, the PBS extract of the hydrogel was used instead of the hydrogel to complete the experiment. The CCK-8 cytotoxicity results showed that ( Figure 7 ), the cell viability of cells cultured in the hydrogel extract reached more than 90% after 24 hours, and the SDSS-loaded hydrogel BSP / CS / β-GP@SDSS was as safe and non-toxic as BSP / CS / β-GP.

[0053] (8) Analysis of hydrogel cell proliferation performance

[0054] The CCK-8 in vitro method was used to detect the effects of BSP / CS / β-GP and BSP / CS / β-GP@SDSS prepared in Comparative Example 1 and Example 1 on the proliferation of HaCat. In this experiment, the PBS extract of the hydrogel was used instead of the hydrogel to complete the experiment. The CCK-8 cell proliferation results showed that ( Figure 8 ), the dilution multiple of the hydrogel extract increased, and the proliferation performance weakened. The empty and drug-loaded hydrogels maintained a high cell proliferation activity within 72 hours, and the addition of SDSS further improved the cell proliferation performance of the BSP / CS / β-GP hydrogel system.

[0055] (9) Analysis of hydrogel cell migration performance

[0056] The Transwell assay was used to verify the ability of BSP / CS / β-GP and BSP / CS / β-GP@SDSS prepared in Comparative Example 1 and Example 1 to promote the migration of HaCat cells. The migration experiment is shown in the figure ( Fig. 9). The cell coverage area of ​​the BSP / CS / β-GP hydrogel group was significantly larger than that of the control group, and the cell coverage area of ​​the BSP / CS / β-GP@SDSS hydrogel group was significantly larger than that of the BSP / CS / β-GP hydrogel group, which indicates that BSP has the unique property of promoting cell migration, and SDSS further enhances the cell migration ability.

[0057] (10) Animal model experiment on hydrogel skin healing

[0058] The wound healing ability of the BSP / CS / β-GP@SDSS hydrogel prepared in Example 1 was evaluated using a skin trauma mouse model. In this experiment, a wound healing model was constructed using male KM mice weighing 18-22g. The mice were adaptively fed for 5 days, and the mice were anesthetized by intraperitoneal injection of sodium pentobarbital (40mg / kg). The back hair of the mice was shaved and the exposed skin was cleaned, and then a full-thickness skin wound with a diameter of 10mm was cut with ophthalmic scissors. The wound next to the sterile ruler was photographed to measure the wound area. The wound healing properties of BSP / CS / β-GP@SDSS hydrogel were evaluated using an experimental group and a blank group. BSP / CS / β-GP@SDSS hydrogel was sterilized by ultraviolet irradiation. The experimental group introduced a BSP / CS / β-GP@SDSS hydrogel with a thickness of 0.5cm into the wound bed, and the control group did not perform wound treatment. The experimental group was given drugs by patch application on day 0, day 3, day 7, day 10 and day 14, respectively. Wounds were measured and photographed on day 0, day 3, day 7, day 10, day 14 and day 16, respectively. Wound tissues of mice were collected on day 16 and preserved in paraformaldehyde. The samples were stained with HE and Masson, scanned, and the histological characteristics of the wound sections were examined.

[0059] The results of animal experiments are shown in the figure ( Fig.10 ), on the 3rd day, the treated wound was significantly smaller, and the wound exudate had been absorbed by the hydrogel, which proved that the hydrogel wound dressing has the effect of absorbing wound exudate and accelerating wound healing in the early stage of the wound. On the 7th day, the wound of the treated group was closed and the wound was further reduced. The overall wound surface had new skin tissue formation, while the untreated group was still in the coagulation stage. On the 11th day, the wound of the treated group was significantly smaller than that of the untreated group and entered the tissue remodeling stage, while the untreated group still had exudate. On the 16th day, the wound healing rate of the treated group was 97.05%, which was basically healed, while the healing rate of the untreated group was lower and there was still a wound. H&E staining results ( Fig.11 ) showed that a large number of cells accumulated at the wound surface of the BSP / CS / β-GP@SDSS hydrogel group, and the new epidermal cells covered the wound surface, showing the formation of complete epidermis or subcutaneous appendages, while the accumulation of epidermal cells in the blank group was less and could not cover the subcutaneous tissue; Masson staining ( Fig.11) showed that the wound of the BSP / CS / β-GP@SDSS hydrogel-treated group had a large number of muscle fibers and collagen fibers, while the blank group had only a small amount of collagen fibers and no muscle fibers. This proves that BSP / CS / β-GP@SDSS hydrogel promotes wound healing by accelerating the generation of collagen fibers and muscle fibers, and has potential value in the field of skin regeneration. This confirms that the BSP / CS / β-GP@SDSS hydrogel has the function of promoting wound healing and improving repair efficiency, and has potential development value in the field of skin regeneration research.

Claims

1. A Bletilla striata polysaccharide composite hydrogel capable of sustained-release of sodium danshensu, characterized in that: The hydrogel has a pore size of 10-50 μm and can slowly release small molecule sodium tanshinone.

2. The Bletilla striata polysaccharide composite hydrogel capable of sustained-release of sodium danshensu according to claim 1, characterized in that: The pore size of the hydrogel is 20-30 μm.

3. The Bletilla striata polysaccharide composite hydrogel capable of sustained-release of sodium danshensu according to claim 1, characterized in that: The Bletilla striata polysaccharide composite hydrogel does not contain a cross-linking agent.

4. A method for preparing a Bletilla striata polysaccharide composite hydrogel capable of sustained-release of sodium danshensu, characterized in that: The sodium danshensu solution is directly added to the chitosan solution and stirred thoroughly. The chitosan solution loaded with sodium danshensu and the sodium β-glycerophosphate solution are then mixed in an ice bath. The bletilla striata polysaccharide solution is then added at room temperature. The chitosan loaded with sodium danshensu, sodium β-glycerophosphate, and bletilla striata polysaccharide are cross-linked in a molecular entanglement manner to obtain a bletilla striata polysaccharide composite hydrogel.

5. The preparation method according to claim 4, characterized in that: The cross-linking temperature is 20-37°C, and the cross-linking time is 1-5 minutes.

6. The preparation method according to claim 4, characterized in that: The mass ratio of chitosan: sodium β-glycerophosphate: bletilla striata polysaccharide in the composite hydrogel is 3:(7-15):(6-12), and the mass ratio of chitosan: sodium danshensu is (18-22):

1.

7. Use of the Bletilla striata polysaccharide composite hydrogel according to claim 1 in the preparation of a drug for promoting in vitro wound healing.

Citation Information

Cited By

  • Injectable hyriopsis cumingii shell matrix protein-bletilla striata polysaccharide hydrogel as well as preparation method and application thereof

    CN122424405A